(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2015)
The present paper describes a reverse phase HPLC method for simultaneous estimation of Trifluoperazine and Isopropamide from their combined tablet dosage form. The proposed RP-HPLC method utilizes an Agilent Zorbax, C18 column (250 × 4.6 mm, 5μm particle size) using a mobile phase consisting of mixture of Buffer: Acetonitrile (80: 20 v/v) mobile phase flow rate of 0.8 ml/min; and UV detection at 227nm. The retention time for Trifluoperazine and Isopropamide were 2.4 and 3.62 minutes respectively. The method was linear in the range of 40-120μg/ml and 100-300μg/ml and correlation coefficients were 1.00 and 1.00 for Trifluoperazine and Isopropamide respectively. The limit of detection was found to be 2.963 and 2.985µg/ml for Trifluoperazine and Isopropamide respectively. Limit of quantification was found to be 9.877 and 9.9502 for Trifluoperazine and Isopropamide respectively. The percentage recoveries for Trifluoperazine and Isopropamide ranged from 100.03-100.36% and 100.00-100.07 % respectively. The percentage of RSD for precision of the method was found to be less than 2%. The proposed method can be used for the routine analysis for the estimation of these drugs in combined dosage form.